Financování a zadávání veřejné stavební investice z pohledu investora - Sedlaříková, Zuzana (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tato práce se věnuje problematice zadávání a financování veřejných zakázek. V teoretické práci je popsáno, jaké subjekty působí na stavebním trhu a jak se stavební zakázky dělí. Práce je zaměřena na veřejné zakázky a veřejného zadavatele a jejím cílem je zanalyzovat finanční situaci a financování určité stavební zakázky a navrhnout pro ni alternativní způsoby financování.

This thesis deals with the issue of procurement and financing of a public contracts. The theoretical part of this thesis describes the entities that are active in the construction market and how the construction orders are divided. The thesis is focused on the public procurement and the public contracting authority and the objective is to analyze the financial situation and financing of a particular construction contract and propose alternative ways of financing.
Financing and procurement of construction investment from the aspect of investor
Keywords: Veřejná zakázka; financování; státní rozpočet; účastníci stavebního trhu; fondy Evropské unie; dotace; veřejná správa; výběrové řízení; Statutární město Opava.; Public procurement; financing; state budget; construction market participants; European Union funds; subsidies; public administration; tender; Statutory city of Opava.